PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI MELALUI MOTIVASI TERHADAP KINERJA KARYAWAN PADA BALAI PERIKANAN BUDIDAYA AIR PAYAU (BPBAP) SITUBONDO - Hasbiadi Hasbiadi; Rizal Rizal; Merry Puspita Dyah Utami (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
One of aquaculture supporting organization in Indonesia is Balai Perikanan Budidaya Air Payau (BPBAB) which located in Situbondo regency, Province of East Jawa. Performance appraisal is used to achieve the target production of aquaculture. The function of this research are to determine the influence factors of BPBAP Situbondo employee performance by using motivation as intervening variable. This research is explanatory research by using SEM analysis. The result show that leadership style variable is directly and significantly influence to motivation variable, organizational culture variable is directly and significantly influence to motivation variable, and motivation variable is directly and significantly influence to performance appraisal variable, leadership style is not influence to performance appraisal variable if motivation as intervening variable but organizational culture variable is directly and significantly influence to performance appraisal variable by motivation variable or without motivation variable as intervening. Key words: BPBAP Situbondo, Motivation, Performance, SEM